PENYELESAIAN KREDIT BERMASALAH PADA PERJANJIAN PINJAMAN ANTARA UNIT PENGELOLA KEGIATAN LEMBAGA KESWADAYAAN MASYARAKAT FAJAR GEMILANG DENGAN KELOMPOK SWADAYA MASYARAKAT KELURAHAN MUARA FAJAR TIMUR KOTA PEKANBARU - Martuah, Ali; Bachtiar, Maryati; Darnia, Meriza Elpha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Revolving economic loans are an activity carried out by Community Self-SufficiencyAgencies/Institutions through the Activity Management Unit (UPK) to provide capital to poorpeople through a group mechanism and returned in installments. The advantage of this pro-gram is that there is no collateral requirement as a condition for entering into a credit agree-ment. Unsecured loans are very vulnerable to failure to pay credit. The aims of this researchare; Firstly, to find out what factors cause problematic credit to occur in the Revolving Fundloan agreement between the Fajar Gemilang Community Self-Help Institution UPK and theMuara Fajar Timur Village Community Self-Help Group, Pekanbaru City. And secondly,knowing how to resolve problem loans in the Revolving Fund loan agreement between theFajar Gemilang Community Self-Help Institution UPK and the Muara Fajar TimurCommunity Self-Help Group, Pekanbaru City.The type of research used is sociological research, sociological research is a study thatexamines legal aspects by looking at applicable laws and regulations and comparing themwith implementation in the field. The location of the research was at the Activity ManagementUnit of the Fajar Gemilang Community Self-Reliance Institution, Muara Fajar Timur Vil-lage, Pekan Baru City. The data sources used are Primary Data, Secondary Data and Ter-tiary Data with Data Collection Techniques using Interviews and Literature Review.The results of this research conclude that the factors causing problematic credit in theFajar Gemilang Activity Management Unit are; First, misuse of credit funds, second, debtorsnot in good faith, third, crop failure in the agricultural sector, fourth, decline in businessturnover, fifth, decline in agricultural selling prices, sixth, absence of BI Checking, seventh,lack of collateral in the loan application process. Efforts to resolve the problem of debtorswho are in default are first, collecting arrears from the debtor's house and giving warningletters I, II and III. Second, settling arrears by forming a debt collection team. As well as res-cuing problematic loans by; Rescheduling (rescheduling), Reconditioning (reconditioning),and Restructuring (rearranging). Collection through legal channels is not recommended inresolving problem loans, prioritizing deliberation and amicable channelKeywords: Credit agreement, Problem Credit, and Revolving Funds.